Comparison of functional recovery capacity among athletes in individual and team disciplines - djelti, tayeb; djamali, merabet; Bensalem, khaled (sports creativity, 2025)
The world is witnessing significant progress in athletic achievements as a result of the continuous efforts of specialists, through the interaction of sports with other sciences such as education, psychology, law, philosophy, chemistry, physiology, sociology, and others. Given the magnitude of this progress, both theoretical and applied, it is imperative that coaches possess a broad understanding of the development of these sciences and be capable of comprehending numerous issues and topics related to athletic training. Knowledge of the fundamental aspects of training, such as planning training programs, selecting athletes, developing individual training components, predicting athletic potential, and all other training matters, necessitates that coaches have extensive knowledge of education, psychology, kinesiology, biology, and other related sciences. Research and studies have contributed to understanding the factors influencing performance development in various sports by developing new training methods that leverage different areas to conserve effort and time. These areas include the physiological aspect, encompassing physiological organs (heart, lungs, and muscles), bioenergetic processes, maximum aerobic capacity (oxygen consumption), physical performance, functional systems, and functional recovery capacity. The latter has become increasingly important for coaches and athletes alike in designing training programs by utilizing the recovery mechanism. The recovery process actually begins during the activity itself, with the rebuilding of energy-producing materials. Recovery is a situational indicator that occurs as soon as an individual stops working, and its duration varies depending on the type of activity, the level of training, and the intensity of the load. Given the importance of functional recovery capacity, we decided to study this indicator by comparing it between some individual sports (swimming and athletics) and team sports (handball and volleyball).